2023
DOI: 10.1002/iid3.897
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Successful treatment of anti‐MDA5‐positive to negative dermatomyositis‐associated interstitial lung disease with the JAK inhibitor tofacitinib

Abstract: Objective: Anti-MDA5 antibody-positive dermatomyositis (DM) is a rare clinical autoimmune disease, and anti-MDA5-positive DM with interstitial lung disease (ILD) is the most important cause of death in DM patients. We reported the efficacy of the JAK1/3 inhibitor tofacitinib as an anti-MDA5negative treatment option for patients with anti-MDA5-positive DM-ILD. Method and process: Here we report a 51-year-old female patient with cough, sputum, shortness of breath for 5 months, rash for 3 months, and muscle pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…2. A total of 21 articles, including 79 cases, were identified [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although Shirai et al [8] reported 13 patients treated with tofacitinib, only 8 patients were included in our analysis because data of the other 5 patients were combined with those treated without tofacitinib.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2. A total of 21 articles, including 79 cases, were identified [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Although Shirai et al [8] reported 13 patients treated with tofacitinib, only 8 patients were included in our analysis because data of the other 5 patients were combined with those treated without tofacitinib.…”
Section: Literature Reviewmentioning
confidence: 99%